The impact of bureaucratic quality on tax revenue collection in democratic settings - Ebenezer Appiah; Na Song; Isaac Appiah-Otoo; Bright Nana Kwame Ahia; Koffi Dumor; Moumbark Toure; Yawovi M. A. Koudalo (Humanities & Social Sciences Communications)
Abstract This study investigated the effect of bureaucratic quality on tax revenue mobilization in Africa while also examining the moderating effect of democracy and corruption in this relationship. Employing the fixed effects technique and panel data for 25 African countries from 1996 to 2021, we found a significant positive association between bureaucratic quality and tax revenue. We also found that democracy significantly raises tax revenue while corruption impedes tax revenue. Furthermore, bureaucratic quality and democracy are complementary drivers of tax revenue, while corruption and bureaucratic quality are substitutes in reducing tax revenue in Africa. The study provided policy implications for African nations seeking to diversify revenue sources and improve bureaucratic quality.